The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2002
DOI: 10.1097/00042307-200203000-00007
|View full text |Cite
|
Sign up to set email alerts
|

Urinary tract infections after renal transplantation

Abstract: Up to now one of the major problems for successful organ transplantation has been the reaction of the immune system of the recipient against the donor organ. This could lead to acute and chronic rejection, and in cases of unsuccessful treatment to the loss of the transplant. In organ graft recipients, immunosuppressive agents are used to prevent or treat rejection episodes and to maintain graft function. Although there is an increasing number of immunosuppressive substances, the immunosuppressive therapy curre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
70
1
10

Year Published

2002
2002
2017
2017

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(84 citation statements)
references
References 66 publications
3
70
1
10
Order By: Relevance
“…I n adults, urinary tract infection (UTI) after renal transplantation has been associated with significant morbidity (1). The use of postoperative antibiotic prophylaxis has reduced dramatically the incidence of UTI after renal transplantation in the past few decades (2,3).…”
mentioning
confidence: 99%
“…I n adults, urinary tract infection (UTI) after renal transplantation has been associated with significant morbidity (1). The use of postoperative antibiotic prophylaxis has reduced dramatically the incidence of UTI after renal transplantation in the past few decades (2,3).…”
mentioning
confidence: 99%
“…The incidence of bacterial infection in renal transplant recipients is directly related to the net immunosuppressive effect achieved and the duration of time over which this therapy is administered. Bacterial urinary tract infections (UTIs) are frequently associated with the early onset of chronic rejection and may also lead to reduced transplant survival (15,18). Studies have shown that in 40 to 60% of transplant recipients the urinary tract is the source of septicemia and that in patients with urosepsis the recurrence rate was approximately 40% (1,13).…”
mentioning
confidence: 99%
“…Differences in the definition of UTI, follow-up period, time of testing and the use of antimicrobial prophylaxis may explain this wide range 3 . Previously bacterial agents isolated from renal transplant recipients with UTI were almost similar to those causing UTI in the general population 4 . In Bangabandhu Sheikh Mujib Medical University (BSMMU) over a period of 2 years from January 2002 to December 2003 Islam et al 5 studied 31 post renal transplant patients of which 51 episodes of bacterial infection occur.…”
Section: Introductionmentioning
confidence: 95%